Oxytetracycline and Streptomycin Resistance Genes in Xanthomonas arboricola pv. pruni, the Causal Agent of Bacterial Spot in Peach - Herbert, Austin; Hancock, C. Nathan; Cox, Brodie; Schnabel, Guido; Moreno, Daniela; Carvalho, Renato; Jones, Jeffrey; Paret, Matthew; Geng, Xueqing; Wang, Hehe (Frontiers in Microbiology, 2022)
Xanthomonas arboricola pv. pruni (Xap) causes bacterial spot, a major worldwide disease of Prunus species. Very few chemical management options are available for this disease and frequent applications of oxytetracycline (OTC) in the United States peach orchards have raised concerns about resistance development. During 2017-2020, 430 Xap strains were collected from ten peach orchards in South Carolina. Seven OTC-resistant (OTCR) Xap strains were found in 2017 and 2020 from four orchards about 20-270 km apart. Interestingly, the seven strains were also resistant to streptomycin (STR). Six strains grew on media amended with ≤100 µg/mL OTC, while one strain, R1, grew on ≤250 µg/mL OTC. Genome sequence analysis of four representative OTCR strains revealed a 14-20 kb plasmid carrying tetC, tetR, and strAB in each strain. These three genes were transferable to Xanthomonas perforans via conjugation, and they were PCR confirmed in all seven OTCR Xap strains. When tetC and tetR were cloned and expressed together in a sensitive strain, the transconjugants showed resistance to ≤100 µg/mL OTC. When tetC was cloned and expressed alone in a sensitive strain, the transconjugants showed resistance to ≤250 µg/mL OTC. TetC and tetR expression was inducible by OTC in all six wildtype strains resistant to ≤100 µg/mL OTC. However, in the R1 strain resistant to ≤250 µg/mL OTC, tetR was not expressed, possibly due to the presence of Tn3 in the tetR gene, and in this case tetC was constitutively expressed. These data suggest that tetC confers OTC resistance in Xap strains, and tetR regulates the level of OTC resistance conferred by tetC. To our knowledge, this is the first report of OTC resistance in plant pathogenic xanthomonads.